2005
DOI: 10.1111/j.1540-5907.2005.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Who Wants to Globalize? Consumer Tastes and Labor Markets in a Theory of Trade Policy Beliefs

Abstract: Although the allure of consumption is the engine of globalization, political economists have tended to ignore varying consumer tastes as a potential source of beliefs about trade policy. This article develops a theory of trade policy preferences that adds the notion of varying consumer tastes to the standard labor-market application of the Heckscher-Ohlin trade model. The theory, which can explain trade preferences both across individuals and countries, is supported by an empirical analysis of survey data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
110
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(111 citation statements)
references
References 40 publications
1
110
0
Order By: Relevance
“…This came with a significant increase in the amount of leisure time available and (in many jobs) a decline in the dangers and exhaustion associated with them (Schorr 1999). Simply put, people felt they were living much better thanks to the market (Baker 2005, Emmott 2003, Inglehart et al 2008, and many actually were (and not just in terms of electronics per capita, but also as measured by indicators such as the Human Development Index). The issue is not to question the 1990s boom, but to challenge the assumption that market fundamentalism was solely responsible for it.…”
Section: The Culture Of Neoliberalismmentioning
confidence: 97%
“…This came with a significant increase in the amount of leisure time available and (in many jobs) a decline in the dangers and exhaustion associated with them (Schorr 1999). Simply put, people felt they were living much better thanks to the market (Baker 2005, Emmott 2003, Inglehart et al 2008, and many actually were (and not just in terms of electronics per capita, but also as measured by indicators such as the Human Development Index). The issue is not to question the 1990s boom, but to challenge the assumption that market fundamentalism was solely responsible for it.…”
Section: The Culture Of Neoliberalismmentioning
confidence: 97%
“…Trade theories (Heckscher-Ohlin and Ricardo-Viner) predict the effect of trade expansion on both wages ("jobs") and prices ("consumption"; Baker, 2005;Helpman, 2011); yet, the majority of studies on trade attitudes measure respondents' trade interests with how they earn money (e.g., skill levels and sectors of employment), not how they spend money. 5 Exceptions are a series of studies done by Baker (2003Baker ( , 2005Baker ( , 2009, which have shown that consumers of imported and import-competing goods favor free trade and that this is why trade reforms were popular among Latin American citizens. 6 A paradox for advanced industrialized nations is that low-income citizens' opinions toward trade can be torn between the duality of interests they have as both income-earners ("protectionist") and consumers ("free trade"), as discussed previously.…”
Section: The Puzzle: Producer Consumer and Individual Support For Fmentioning
confidence: 99%
“…Therefore, regardless of the abundance of labour in Latin American countries, systemic developments in the global economy limit the ability of unskilled workers to fully exploit their advantage. 4 Baker (2003Baker ( , 2005 is another example of work that questions the extent to which we see strict factoral divisions on trade. He argues that trade preferences do not reflect class-based divisions because voters are also consumers and, therefore, frequently oppose the higher costs associated with trade protection.…”
Section: Notesmentioning
confidence: 98%
“…3 Some scholars assert that unskilled labourers in Latin America fail to reach a minimum threshold of skill to be able to compete in export-oriented manufacturing (Seligson, 1999;Mamoon, 2007;Baker, 2003;Wood, 1997Wood, , 1994. Pursuant to this 'human capital model' of trade preferences, many workers cannot take advantage of their presumed cost-based advantage in international trade (Baker, 2005;Wood, 1997). Therefore, regardless of the abundance of labour in Latin American countries, systemic developments in the global economy limit the ability of unskilled workers to fully exploit their advantage.…”
Section: Notesmentioning
confidence: 99%